2019
DOI: 10.1167/iovs.19-27472
|View full text |Cite
|
Sign up to set email alerts
|

The Oxygen Saturation in Vascular Abnormalities Depends on the Extent of Arteriovenous Shunting in Diabetic Retinopathy

Abstract: PURPOSE. Diabetic retinopathy is characterized by disturbances in retinal blood flow mediated by capillary occlusion, intraretinal microvascular abnormalities (IRMAs), neovascularizations, and omega loops and reduplications. It is likely that the study of oxygen saturation in these abnormalities can provide knowledge about their role in the development of diabetic retinopathy. METHODS. The oxygen saturation in IRMA vessels and venous loops and reduplications were studied in 40 diabetic patients with severe non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…[40][41][42] This might explain the increased oxygen saturation in the larger venules with increasing severity of diabetic retinopathy. 43,44 The need for an increased shunting capacity to circumvent the capillary bed might also potentially contribute to the development of intraretinal microvascular abnormalities (intra-retinal microvascular abnormalities (IRMA) vessels) 16 and neovascularizations. 15 A transformation of the functional changes in capillary blood flow into irreversible capillary damage might explain postmortem observations of glial cells that have invaded the lumen to obliterate the capillaries in retinal vascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42] This might explain the increased oxygen saturation in the larger venules with increasing severity of diabetic retinopathy. 43,44 The need for an increased shunting capacity to circumvent the capillary bed might also potentially contribute to the development of intraretinal microvascular abnormalities (intra-retinal microvascular abnormalities (IRMA) vessels) 16 and neovascularizations. 15 A transformation of the functional changes in capillary blood flow into irreversible capillary damage might explain postmortem observations of glial cells that have invaded the lumen to obliterate the capillaries in retinal vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to studying blood flow in the smaller retinal vessels that are difficult to resolve is to evaluate the metabolic consequences of changes in the microcirculation using oximetry. 14 With this approach, it has been shown that the oxygen saturation is higher in venules draining the macular area than the retinal periphery 12 and that retinal neovascularizations 15 and microvascular abnormalities 16 in diabetic retinopathy act as arteriovenous (A-V) shunts that can bypass areas of capillary occlusion. However, the effects of normal physiologic regulation of retinal blood flow on oxygen saturation in different parts of the retina have not been studied in detail.…”
mentioning
confidence: 99%
“…Such a parameter might be the oxygen saturation in the larger retinal vessels that can be measured by dual wavelength retinal oximetry [7,8]. Using this technique, the bypassing of the retinal capillary bed in diabetic retinopathy has been confirmed by an increased oxygen saturation in intraretinal shunts [6] and neovascularizations [9]. The resulting increase in oxygen saturation in retinal venules has been documented in a number of studies [10][11][12][13][14][15][16][17][18][19][20][21] although one study found a trend towards a decrease [22].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia, which results from capillary occlusions, is assumed to stimulate the release of growth factors that initate the formation of new vessels to result in proliferative diabetic retinopathy [ 4 ]. The occlusion of retinal capillaries also stimulates the formation of shunt vessels to bypass the occluded retinal areas [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The progression to severe diabetic retinopathy is associated with widening of large retinal venules (>120 μm), 43,44 possibly related to development of retinal arteriole to venule shunts that bypass the diminished perfusion of capillaries. 45,46 The impact of different stages of diabetes on the diameter of small retinal venules in humans, as evaluated in the present study, remain to be determined. Nonetheless, our findings herein provide new insight that early exposure to hyperglycemia in diabetes may influence vasomotor function of human retinal venules.…”
Section: Discussionmentioning
confidence: 92%